The essential guide to doing your research project - O'Leary, Zina; Tennent, Emma (California, United States : Sage Publishing Ltd., 2025)
'Doing a research project or dissertation can be daunting, but this practical book will help you dive straight in, driving each step of the process with confidence. Packed with features to support your learning, this guidebook gives you invaluable advice at each stage, from picking a topic, designing your study and navigating ethics to collecting and analysing data then sharing your findings. This fifth edition empowers you to be critical and self-reflective when consuming and doing research, equips you with the skills to make good decisions, prepare effectively, and take charge of your own project and draws on over XX case studies of real-world research to inspire your creativity and curiosity'--
Keywords: Research -- Methodology; Research -- Methodology -- Study and teaching (Graduate).; Social sciences -- Research